Interpretation of Radio-Echo Sounding Data on a Temperate Mountain Glacier from its Surface - Luchininov, V. S.; Macheret, Yu. Ya. (Journal of Glaciology, 1975)
Temperate mountain glaciers have specific peculiarities which make the interpretation of radio-echo sounding data much more difficult than for polar ice sheets. On the A or Z indicators one can observe a plurality of pulses differing in shape, amplitude, and range. Often a gap is observed on the film. The problem is to select the pulses from the bed or internal reflecting horizon and to reconstruct the subglacial relief or internal interface. During preliminary processing, the radio-coordinates of all marks on a type A radiogram are written into a table. Then non-informative marks are eliminated and informative marks are situated on a continuous line or trace. We put into practice three methods of interpretation: (1) an envelope method, (2) Harrison’s transformation method, (3) approximation of segments of a trace by straight lines. Harrison’s transformation method is the most general one; the others are useful for the presentation of results in a graphical form. The suggested methods are used for the interpretation of the data from a transverse profile of the valley glacier Lednik Bezengiy, Caucasus, 1970-71. Radar RW-10 with a carrier frequency of 440 MHz and overall receiver sensitivity relative to the transmitter pulse power 130 dB was used. It was revealed that the transparency of the glacier changes from year to year. The maximum ice thickness measured was 33°±15 m. Some extended interfaces in the body of the glacier were discovered. One of them, 80 m deep, coincides with seismic contrast interface and with the 0° C isotherm. Radio-echo sounding data are in agreement with gravity measurements on the same profile.